Assessing Economic Impacts of Plant-Based Meat Alternatives on U.S. Retail and Food Service Markets for Animal Protein - Ufer, Danielle; Tonsor, Glynn T. (Nurture, 2026)
Plant-based proteins have a long history in U.S. food markets and innovations in recent years have led to a new class of plant-based meat alternatives (PBMA) becoming commercially available in both retail and food service settings. Early market indicators for PBMA products, including company stock valuations, as well as qualitative excitement over novel offerings and widespread proliferation in food service outlets, pointed to high growth potential and strong consumer interest. However, the market has slowed and adjusted to the availability of PBMA, it has become less clear how PBMA affect overall protein markets, specifically animal proteins. The article addresses the relative value (as measured in willingness to pay estimates) consumers have for various animal and plant-based proteins in both the retail and food service cases. It then simulates market shares to examine prevalence of PBMA in consumer spending and subsequently estimates the consumer welfare impacts of PBMA availability in both types of markets. To further investigate the distribution of PBMA value and impacts across consumer types, these analyses are also broken down by self-reported consumer dietary patterns (Regular meat consumption, flexitarian, vegetarian, and vegan).